Tax incentives as a solution to the uninsured: evidence from the self-employed - Gulcin Gumus; Tracy L. Regan (Institute for the Study of Labor (IZA), 2007)
Between the years 1996 and 2003, a series of amendments were made to the Tax Reform Act of 1986 (TRA86) that gradually increased the tax credit for health insurance purchases by the self-employed from 25 to 100 percent. We study how these changes in the tax code have influenced the likelihood that a self-employed person has health insurance coverage as the policy holder of the plan. The Current Population Survey (CPS) is used to construct a data set corresponding to 1995-2005. The empirical analysis is performed for prime-age men and women, and accounts for differences in family structure and potential eligibility. The difference-in-difference estimates suggest that the series of tax credits did not provide sufficient incentives for the self-employed to obtain health insurance coverage. Estimates of the price elasticity of demand confirm the limited response to changes in the after-tax health insurance premium. The effect was largest, however, among the single men and women in our sample, suggesting that a 10 percent decrease in the after-tax price increases the likelihood of coverage by 0.68 and 1.02 percentage points, respectively.
Keywords: 330; Selbstständige; Krankenversicherung; Steuerbegünstigung; USA